Active protein and calcium hydroxyapatite bilayers grown by laser techniques for therapeutic applications. Issue 9 (20th February 2013) - Motoc, M. M.; Axente, E.; Popescu, C.; Sima, L. E.; Petrescu, S. M.; Mihailescu, I. N.; Gyorgy, E.
<x xml:space="preserve">Abstract</x> Active protein and bioceramic calcium hydroxyapatite (HA) bilayers were grown by combining conventional pulsed laser deposition (PLD) and matrix–assisted pulsed laser evaporation (MAPLE) techniques. A pulsed UV KrF* excimer laser was used for the irradiations. The HA layers were grown by PLD. Proteins with antimicrobial action were attached to the bioceramic layers using MAPLE. The composite MAPLE targets were obtained by dissolving the proteins powder in distilled water. The crystalline status and chemical composition of the obtained structures were studied by X‐ray diffractometry and Fourier transform infrared spectroscopy. The layers were grown for the design of advanced future metal implants coatings, ensuring both enhanced bone formation and localized antimicrobial therapy. Our results demonstrated that protein coatings improve bone cell proliferation in vitro. Immunofluorescence experiments show that actin filaments stretch throughout bone cells and sustain their optimal spreading. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2706–2711, 2013.